The Influence of Edugame Wordwall Media on Students’ Ability to Solve Mathematical Problems - Zahra Maulitya Putri; Ayu Tsurayya (Pendidikan Matematika UNIMOR, 2024)
The ability of mathematical problem-solving is a crucial element in a mathematical learning process that allows learners to deepen their understanding comprehensively. To overcome the various challenges that arise in this process, effective learning solutions are needed, including the use of tools or media such as Wordwall edugame. This study aims to investigate how Wordwall educational games affect the improvement of students' abilities in solving mathematical problems. The study adopted a quantitative experimental method utilizing a Pretest-Posttest Control and quasi-experimental Design, each class consisted of 40 grade VII students selected through a purposive sampling technique. The research utilizes a test as its measuring tool for mathematical problem-solving ability. The statistical test results revealed that using Wordwall edugame had a profound impact on enhancing mathematical problem-solving ability, with a paired sample t-test value of <0.001. After the treatment was applied, the average scores increased significantly, with the experimental class averaging from 18.85 to 53.2 and the control class from 22.83 to 41.83. The experimental class showed a significant improvement before and after the treatment, while the control class did not show a significant change in this study, indicating that using Wordwall edugame media significantly improved math problem-solving ability.